LANGUAGE FUNCTION ACQUISITION OF THREE-YEAR-OLD CHILDREN IN URBAN EDUCATED FAMILY ENVIRONMENT - Kurniasari, Anita Dewi; Nasucha, Yakub; Al-Ma’Ruf, Ali Imron (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2020)
This article aims to describe the acquisition of language function of three-year-olds in an urban educated family environment. This research utilizes a qualitative approach with a descriptive method. The research subjects are three-year-old children in an educated family environment in the city of Surakarta with a focus on language function. Data are obtained in school, family, and home environment. Data collection uses observation, recording, and note-taking techniques. Data analysis is performed using the translational, phonetic, and referential identity methods. Data validation applies to data source triangulation. The results of the research found three language functions acquired, including information function, exploration function, and persuasion function. The information function is obtained through the stimulation of the school environment, family environment, and play environment. The exploration function is utilized to convey the results of children's learning development. The function of persuasion is used by children to invite or seduce other people. It can be concluded that the three-year-old children are capable of acquiring various language functions with enough vocabulary to utilize them and stimulations at this stage are important and thus encouraged.